Retirement benefit plans: Accounting disclosures and stock returns - Lode, Nor Asma (Universiti Utara Malaysia, 2006)
Given that Malaysian companies have to adhere to the new standard regarding Retirement Benefit Reporting (FRS 119) for their 2003 financial statements and thereafter, this study seeks to find out the disclosure practices before and after the effective date of introducing the new standard. The findings show that 36 companies complied with FRS 119 before the effective date and 166 companies complied with the FRS 199 after the effective date.It is worth finding that the extent of disclosures of FRS 119 has improved after the effective date especially the disclosure on method of actuarial valuations, total expense recognized in the income statement and the principal actuarial assumptions.This study also finds that there is a marginally significant association between the type of retirement benefit plans and firm specific characteristics that are firm size and type of industry.On the other hand, this result reveals that the Cumulative Market Adjusted Return (CMAR) is positive and significant for both the early and non-early adopters.